LoRaWAN based early flood alert system using CoAP Protocol. Issue 1 (1st December 2022) - Raju, C.; Krishnamoorthi, M.; Hari, K.; Moses, M.Leeban
Abstract: Flood monitoring is important to reduce the impact of disaster to save lives of people and animals. At present existing systems lack in providing autonomous and infrastructure independent services to stakeholders. Therefore, Alerting flood early gaining interest among nations worldwide to prevent the loss of human life and economic losses. To gather more sensor data for predicting floods with advanced networking standards are important. At present flood alert systems mostly depend on the satellite based or infrastructure based communication systems. As a result, cost and complexity of the system increases. In this paper an idea to implement a flood warning system based on LoRaWAN and non-proprietary hardware and protocol was proposed. Our proposed project overcomes existing infrastructure based dependent services to self-made autonomous services for miles.